Comparison of somatotype and speed in competitive swimming at different phases of training - Araújo, C. G. S.; Pavel, R. C.; Gomes, P. S. (Swimming III. Proceedings of the Third International Symposium of Biomechanics in Swimming, University of Alberta, Edmonton, Canada, 1979)
This study was done to analyze the relationship between ratings of somatotype components and sprinting speed in the water of competitive swimmers at four different phases of their training.